PENGEMBANGAN VIDEO TUTORIAL DALAM PEMBELAJARAN TATA RIAS KARAKTER - Ledi Indah Sari, Komang (Universitas Pendidikan Ganesha, 2024)
The purpose of this research is to 1) describe the procedure for making character makeup learning videos. 2). Experts in media production and content creation explain the feasibility of character makeup tutorial videos as learning tools. This research is R&D research, using a three-stage planning, production, and evaluation formula known as the PPE development model. This research uses both qualitative and quantitative data, with the latter serving as the main method of analysis. This study uses observation, interviews, and questionnaires to collect data. Six semester 4 cosmetology students at the Ganesha University of Education with a specialization in Family Welfare Education were tested in small groups, together with two material experts and two media experts. The research results show that the steps for making a Character Makeup tutorial video go through the following stages: planning in determining the character makeup design, production of making a video tutorial, evaluating the feasibility of a video tutorial through a small group test of 6 students. The feasibility of video tutorials in learning character make-up gets the results of the media expert validation test with a percentage of 93.3% then the results of the material expert validation test get a percentage of 84.6% so that the video tutorial is said to be feasible and does not need to be revised. The results of the average percentage of the target subject's responses were 92.36% so that the video was said to be very good without revision.